2012
DOI: 10.1167/iovs.12-10020
|View full text |Cite
|
Sign up to set email alerts
|

A Neurobehavioral Analysis of the Prevention of Visual Impairment in the DBA/2J Mouse Model of Glaucoma

Abstract: PURPOSE. Timoptic-XE treatment was used to examine the relationship between age-related changes in intraocular pressure (IOP), retinal cell loss, visual ability, and neuronal labeling in the superior colliculus in the DBA/2J mouse model of pigmentary glaucoma.METHODS. Mice were administered Timoptic-XE (0.0%, 0.25%, or 0.50%) daily from 9 weeks to 12 months of age. Visual ability and IOP were evaluated at 3, 6, 9, and 12 months of age. Mice from each group were then given intraocular injections of wheat germ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 53 publications
2
30
0
1
Order By: Relevance
“…Mammalian eyes subjected to weeks to months of IOP elevation undergo neuronal, glial, and connective tissue alterations that are phenotypically similar to humans (Morrison et al, 1990(Morrison et al, , 1997Soto et al, 2011). In addition, IOP lowering slows RGC loss in animal model eyes (Wong and Brown, 2012) as it does in humans. A monkey model of elevated IOP (Gaasterland and Kupfer, 1974; has been extensively used to study glaucoma changes in the retina, ONH (Morrison et al, 1990), and brain (Weinreb et al, 1994).…”
Section: Role Of Experimental Animal Modelsmentioning
confidence: 95%
“…Mammalian eyes subjected to weeks to months of IOP elevation undergo neuronal, glial, and connective tissue alterations that are phenotypically similar to humans (Morrison et al, 1990(Morrison et al, , 1997Soto et al, 2011). In addition, IOP lowering slows RGC loss in animal model eyes (Wong and Brown, 2012) as it does in humans. A monkey model of elevated IOP (Gaasterland and Kupfer, 1974; has been extensively used to study glaucoma changes in the retina, ONH (Morrison et al, 1990), and brain (Weinreb et al, 1994).…”
Section: Role Of Experimental Animal Modelsmentioning
confidence: 95%
“…In D2 mice, high IOP causes RGC loss that can be prevented by IOP-lowering interventions (28)(29)(30)(31). Importantly, glaucoma in D2 mice is an axonopathy, as evidenced by substantial RGC protection in the presence of the Wallerian degeneration slow allele (D2.Wld s ) (20).…”
mentioning
confidence: 99%
“…However, we did not note any adverse effects to drugs during our investigation [21]. Previous reports about DBA/2J mice evaluated the effects of clinically used antiglaucoma medicine [21,27]. Schuettauf et al [21] reported that daily administration of timolol eye drops could prevent retinal ganglion cell loss.…”
Section: Discussionmentioning
confidence: 72%
“…However, they did not refer to IOP changes during their experiments. Another report showed that daily administration of Timoptic XE eye drops for 12 months resulted in retinal ganglion cell survival with IOP reduction [27]. Surprisingly, there is no report describing the short-term IOP-lowering effects of antiglaucoma medicines specifically concerning DBA/2J.…”
Section: Discussionmentioning
confidence: 99%